Comparison of Dental Caries and Oral Hygiene Status of Children in Suburban with those in Rural Population of Southwestern Nigeria - Titus Ayodeji Oyedele; Yewande I. Adeyemo; Adeola M. Ladeji; Adekunle M. Adetayo; Chioma L. Nzomiwu (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare prevalence of dental caries, oral hygiene status and associated risk factors of children in suburban and rural communities in the Southwest region of Nigeria. Material and Methods: Secondary data was extracted from cross-sectional researches conducted in two study locations involving 8 to 12 year olds.  Data retrieved included age, gender, family structure, socioeconomic status, oral hygiene and dental caries. Caries assessment was done using WHO Oral Health Survey methods. Oral hygiene data was collected using Simplified Oral Hygiene Index (OHI-S) by Greene and Vermillion. Statistical significance was established at p<0.05. Results: The prevalence of dental caries in Group A and Group B study participants were 13.4% and 22.2% respectively. Children from rural community had significant higher caries prevalence (p=0.00) and poorer oral hygiene (P=0.00) compare with their counterparts in the suburban community. There was a significant association between oral hygiene, age and dental caries in suburban participants (p=0.02) while among the rural participants there was significant association between gender and dental caries (p=0.04). Children with poor oral hygiene have increased odds of having dental caries compared to children with good oral hygiene in the two study communities. Conclusion: Dental caries was more prevalent among the rural dwellers than the sub-urban dwellers. There is a need to make oral health care services/products available, accessible and affordable for the rural community.